Influence of Blockchain and Artificial Intelligence on Audit Quality: Evidence from Indonesia - Wardani, Nadia Amalia; Suryaningrum, Diah Hari (Journal of Business Management and Economic Development, 2026)
The purpose of this study is to investigate the impact of blockchain technology and artificial intelligence (AI) on audit quality through the participation of auditors from Indonesian Public Accounting Firms (KAP).  The conceptual framework for this study is based on Agency Theory and the Technology Acceptance Model (TAM), which describe how technological advancements might improve auditors' performance and accountability by eliminating knowledge asymmetry between agents and principals.  Primary data from 207 respondents were gathered using a convenience sampling method.  The study used a quantitative research design with a survey disseminated to auditors via structured questionnaires. The SmartPLS 4 software was used to perform data analysis utilizing the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique.  The findings show that blockchain technology improves audit quality by increasing transparency, correctness, and dependability of audit data via real-time and immutable transaction recording.  Furthermore, artificial intelligence (AI) improves audit quality by supporting auditors in finding abnormalities, assessing risks, and expediting the audit process via automated data analysis.